Evaluation of two communication tools, slideshow and theater, to improve participants' understanding of a clinical trial in the informed consent procedure on Pemba Island, Tanzania. - Marta S Palmeirim; Ulfat A Mohammed; Amanda Ross; Shaali M Ame; Said M Ali; Jennifer Keiser (Public Library of Science (PLoS), 2021)
Background Clinical trial participants are required to sign an informed consent form (ICF). However, information is lacking on the most effective methods to convey trial relevant information prior to inviting participants to sign the ICF, being particularly pertinent in low-income countries. A previous study on Pemba Island, Tanzania, found that a verbal information session (IS) was significantly better than providing an ICF alone. However, knowledge gaps remained. Building on these findings, we investigated the effect of adding a slideshow or a theater to the IS in the informed consent procedure of an anthelminthic clinical trial. Methodology/principal findings A total of 604 caregivers were randomized into the control group that only received an ICF (n = 150) or an ICF plus one of three intervention strategies: (i) verbal IS (n = 135), (ii) verbal IS with a slideshow (n = 174) or (iii) verbal IS followed by a theater (n = 145). All modes of information covered the same key messages. Participants' understanding was assessed using a semi-structured questionnaire. The mean score of caregivers in the control group (ICF only) was 4.41 (standard deviation = 1.47). Caregivers attending the IS alone were more knowledgeable than those in the control group (estimated difference in mean scores: 2.40, 95% confidence interval (CI) 1.95 to 2.86, p < 0.01). However, there was no evidence of an improvement compared to the IS only when participants attended a slideshow (0.09, 95% CI -0.53 to 0.35, p = 0.68) or a theater (0.28, 95% CI -0.27 to 0.82, p = 0.32). Three out of 10 key messages remained largely misunderstood, regardless of the mode of information group. Conclusions/significance Our study confirmed that, in this setting, an ICF alone was not sufficient to convey clinical trial-related information. An IS was beneficial, however, additional theater and slideshows did not further improve understanding. Future research should explore methods to improve communication between study teams and participants for different key messages, study types and settings.